Evaluation of HER2 cell surface protein expression in differentiated thyroid cancers and its relationship with tumor size and stage - Mozaffar, Mohammad; Moradi, Afshin; khazaeian, danial (Student Research in Translational Medicine, 2021)
Background & Aim: we aimed to evaluate the expression of HER2 marker in differentiated thyroid cancers and its correlation with tumor size and stage. Materials and Methods: this is a cross-sectional study that was performed at Tehran Shohada-E-Tajrish hospital from 2015 to 2019. Patients with differentiated thyroid cancer were enrolled in the study. Patients’ baseline characteristics and tumor properties were recorded. Expression of tumor marker testing was conducted with IHC. Analysis was performed with SPSS version 20. Results: fifty cases of thyroid cancer with a mean age of 46.6 years (78% females) were evaluated. 86% of cases were PTC, 10% FTC, and 4% hurthle cell carcinoma. HER2 positivity rate was 34% totally. HER2 positivity in FTC and PTC patients was 40% and 34.9%, respectively. 84% of patients had a sporadic tumor. HER2 positivity rate in sporadic tumors was 28.6% and 62.5% in familial cases (p=0.063). HER2 status did not correlate with clinicopathologic factors, significantly. Conclusion: with the findings of our study, HER2 can’t be considered a prognostic factor associated with clinicopathologic parameters.